Exploring drawing for animation - Hedgpeth, Kevin (Thomson/Delmar Learning, 2004)
Exploring Drawing for Animation is an innovative introduction to 2D animation and inspirational skill-sharpener for working professionals. The authors creatively link drawing techniques and life drawing -human and animal anatomy, architecture, and scenery- to 2D animation production and outcomes. The instructional format builds animation skills from the ground up, using a technical foundation in drawing as a basis for exploring animation. Overviews span the topics of sequence drawing, character development, motion, proportional techniques, and animation clean-up. Together, these essential skills combine to help readers develop the drawing skills necessary to be a successful animator.